Joint decision-making and power allocation for one-bit feedback sensor communications - Zhang, Xiao Juan. (2013)
We consider a sensor communication scenario where a sensor node communicates information to a data sink. To aid the sensor, the data sink transmits channel state information (CSI). To obtain the CSI, however, a fixed receive processing energy is incurred by the sensor node. Given a choice, the sensor node may choose not to obtain the CSI if the receive processing energy does not lead to a larger reduction in the transmit energy. In this paper, we study the tradeoff involved in this choice. Specifically, we design the optimal transmit strategy so that the total expected transmit and receive power of the sensor are minimized subject to a target outage probability. We focus on the case in which the feedback packet conveys one bit of CSI to the sensor nodes. Closed-form expressions of suboptimal solutions are obtained and shown to perform close to the optimal solution.